Influence of fatty acids in waste cooking oil for cleaner biodiesel - Chuah, L.F. (Springer Verlag, 2017)
Physiochemical properties of biodiesel, a sustainable and green alternative fuel produced from renewable resources, are greatly influenced by the structural features of polyunsaturated, monounsaturated and saturated fatty acids. Two feedstock oils, potentially contribution to cleaner technologies, refined cooking oil and waste cooking oil derived from palm olein have been studied. Fatty acid compositions of the refined cooking oil and waste cooking oil were analysed and confronted with other literature sources. Critical parameters such as cetane number (CN), iodine value, cold filter plugging point (CFPP) and oxidation stability (OS) were correlated with long-chain saturated factor and degree of unsaturation (DU) of fatty acid to match the international standards of cleaner biodiesel. OS in biodiesel has been met with the absence of linolenic acid. High saturated fatty acid provides high CN. The iodine value of feedstock oil met the European standard where the DU of the oils was less than 138. However, CFPP of refined cooking oil and waste cooking oil did not meet the demanding Spanish regional (RD 61/2006) standard due to the presence of stearic and palmitic acid, which tended to clog the fuel filter by precipitating while the biodiesel becomes cool. With the proposed triangular chart for biodiesel properties prediction, potential biodiesel fuels from various feedstock oils can be analysed. © 2016, Springer-Verlag Berlin Heidelberg.